ICCCE 2018 Proceedings of the International Conference on Communications and Cyber Physical Engineering 2018 - Kumar, Amit.; Mozar, Stefan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises selected articles from the International Communications Conference (ICC) 2018 held in Hyderabad, India in 2018. It offers in-depth information on the latest developments in voice-, data-, image- and multimedia processing research and applications, and includes contributions from both academia and industry.
Moving Object Recognition and Detection Using Background Subtraction -- Fog Computing: Overview, Architecture, Security Issues and Applications -- Proposal of Linear Specific Functions for R-L-C as Fundamental Elements in Terms of Considered Specific Electric Constants -- A Viewpoint: Discrimination Between 2 Equivalent Statement of Kirchhoff's Current Law from the Ground of Precedenceness -- An DES Based Mechanism to Secure Personal Data on Internet of Things -- Reputation Based Mechanism to Detect Selfish Nodes in DTN -- Improve Target Detection in Doppler Tolerant Radar using Modified Hex Coding Technique -- Enhance Packet Loss Calculation in Wireless Sensor Networks -- Enhance Packet Loss Calculation in Wireless Sensor Networks -- Enhance Security to MANETs Against Black Hole Attack Using AS Technique -- Design of Smart Water-Saving Irrigation System in Agriculture Based on Wireless Sensor Network for Better Crop Yield -- SVM - A Way to Measure the Trust Ability of a Cloud Service Based on Rank.
Keywords: Wireless communication systems; Mobile communication systems; Signal processing; Telecommunication; Artificial intelligence; Image processing -- Digital techniques; Computer vision; Wireless and Mobile Communication; Signal, Speech and Image Processing; Microwaves, RF Engineering and Optical Communications; Artificial Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Communications Engineering, Networks